User demanded policy routing for multi-homing campus network - Huan-jie ZHANG; Yu-liang XIA (Tongxin xuebao)
Edge router must use policy routing for multi-homing campus network.The flexibility of source address based policy routing defined by network administrator is not sufficient to meet the changing needs of diverse users.One scheme using Linux system was proposed to do user demanded policy routing,which was more flexible and convince than the traditional administrator defined source address based policy routing.Through 10 years of actual use in campus network,It proves that this method can meet the various needs of users,operating stabely and reliablely.